ANALYSIS OF VIEWS ON THE CRITERIA OF INTELLECTUAL ACTIVITY IN ISLAMIC PHILOSOPHY (Scientific journal of the Fergana State University, 2023)
The article analyzes the emergence of Islamic philosophy, its stages, views on rational solutions to the problems of gnoseology, the criteria of scientific and intellektual activity, its axiological and humanistic essence.